Rancang Bangun Aplikasi Analisis Kredit Menggunakan Metode Skoring Pada Bintang Jaya Variasi Audio - Gunawan, Daniel Wijaya; Hartati, Sulis Janu; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
The problem of the research is how to analyze credit customers so as to reduce the risk of mistakes that could cause bad credit payment.Â  BJVA has also been doing analysis credit before giving credit to its customers. But with the analysis, there were still 63% of transactions experienced delay in payment. To reduce the risk of mistakes that could cause bad credit payment, the scoring method will help analyze the customer's credit. Based on trials conducted, only 54 of the transactions can be used as the sample. This application can reduce the risk of bad credit up to 41%.